Comment on "Contemporary Art: Feng Zikai's art thought and its contemporary value" - Yan, Yan (2024)
Commented article: XIE, J. Y.; CHEN, X. M. Contemporary Art: Cultivating Feng Zikai's Teachings. Trans/Form/Ação: Unesp journal of philosophy, v. 47, n. 4, e02400120, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15089.